Seed Oils as Tyrosinase Inhibitors for the Treatment of Hyperpigmentation - Kothapalli, Lata; Dhakane, Tanuja; Bhosale, Komal; Thomas, Asha (Current Enzyme Inhibition, 2024)
Background: Hyperpigmentation is a growing problem worldwide among various skin diseases and directly relates to the quality of life. The factors causing hyperpigmentation may range from excess exposure to sunlight, pollution, underlying disease conditions, adverse effects of a medication, modified lifestyle, and oxidative stress. Treatment includes the use of hydroquinone, retinoids, corticosteroids, and kojic acid along with anti-inflammatory drugs. However, these medications are preferred for short-term treatment under acute conditions, while in the case of long-term treatment, botanical extracts are a safe choice for a majority of the population for the treatment of hyperpigmentation. Formulation with plant extracts/oil enriched with polyphenols, vitamin C, and vitamin E are reported to be safe and effective in inhibiting melanogenesis. Objective: Seed oils composed of polyphenols, vitamins and unsaturated fatty acids were selected to evaluate their antioxidant property and tyrosinase enzyme inhibitory activity. Methods: Grape seed oil (GSO), papaya seed oil (PSO), and carrot seed oil (CSO) were evaluated for their total phenolic and flavonoid content,in-vitro antioxidant activity was done using DPPH assay and anti-tyrosinase activity was done using Mushroom tyrosinase inhibition assay. Results: Total phenolic content for PSO was 0.936 mg/gm. Gallic acid equivalent (GAE) was highest when compared to GSO and CSO, while CSO had a higher total flavonoid concentration, 0.945 mg/gm as quercetin equivalent (QE). Free radical scavenging activity was comparable to standard and tyrosinase inhibitory activity for grape and carrot seed oils were 80.10 % and 76.52 % at 100μg/ml, respectively and was comparable to kojic acid used as standard. Conclusion: The results obtained suggest that the oils can be formulated as a topical depigmenting product and used for skin care and skin glow.
Keywords: Hyperpigmentation